Steatocystoma Multiplex-A Rare Genetic Disorder: A Case Report and Review of the Literature - Hemlata T. Kamra; Pradeep A. Gadgil; Ajay G. Ovhal; Rahul R. Narkhede (Journal of Clinical and Diagnostic Research, 2013)
ABSTRACT A 17 years old female presented with multiple asymptomatic cutaneous cysts all over body, sparing the head and neck region. The microscopic examination of the cysts showed the features of steatocystoma multiplex. This disorder, although it is asymptomatic, is a cosmetic threat to the patient . Only a few cases of the patients with an autosomal dominant mutation, who had keratin 17, have been reported. We are reporting here, a case of steatocystoma multiplex in a 17 years old female, along with its review of literature.